Introduction to Fiber Reinforced Composite (FRC) Post, A New Era in Reinforcing Esthetics: A Case Report (Bangladesh Journal of Dental Research & Education, 2013)
The restoration of a root canal treated or, endodontically treated teeth, is often can be achieved with post and core because of the significant loss of tooth structure. Until the mid-1980s, the safest way to restore an endodontically treated tooth was considered to be the cast-metal post, made indirectly by a dental technician. Also prefabricated metal posts in combination with different core materials under artificial crowns were used. The development and use of fiber reinforced composite (FRC) root canal posts over metallic posts make possible of the attachment & reinforcement of the crown with maximum esthetics. This paper illustrates a technique for rehabilitation of an endodontically treated maxillary central incisor of both sides (UL1 & UR1) with a fiber reinforced composite post (FRC post) & discusses the advantages, disadvantages of metallic post over fiber reinforced composite (FRC) posts.DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16595 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 45-48